With love from Wish & Co. : a novel - Darke, Minnie (Dell Books, 2022)
When an accidental mix-up puts the marriage of Brian, her most prized client, in danger, Marnie Fairchild, the brains and talent behind a personalized gift-buying service, must choose between her head and heart when Brian's gorgeous son Luke enters her life.